Transcriptional Approach for Decoding the Mechanism of rpoC Compensatory Mutations for the Fitness Cost in Rifampicin-Resistant Mycobacterium tuberculosis - Xu, Zhihong; Zhou, Aiping; Wu, Jiawei; Zhou, Aiwu; Li, Jun; Zhang, Shulin; Wu, Wenjuan; Karakousis, Petros C.; Yao, Yu-Feng (Frontiers in Microbiology, 2018)
Multidrug-resistant tuberculosis (TB), defined as TB resistant to the two first-line drugs, isoniazid and rifampin, is a serious challenge to global TB eradication efforts. Although mutations in rpoA or rpoC have been proposed to compensate for this fitness cost due to rpoB mutation in rifampicin-resistant Mycobacterium tuberculosis mutants, the underlying mechanisms remain unclear. Here, we used RNA sequencing to investigate the global transcriptional profiles of 6 rifampin-resistant clinical isolates with either single mutation in rpoB or dual mutations in rpoB/rpoC, as well as 3 rifampin-susceptible clinical isolates. In rifampin-free conditions, rpoC mutation was associated with M. tuberculosis upregulation of ribosomal protein-coding genes, dysregulation of growth-related essential genes and balancing the expression of arginine and glutamate synthesis-associated genes. Upon rifampin exposure of M. tuberculosis isolates, rpoC mutations were associated with the upregulation of the oxidative phosphorylation machinery, which was inhibited in the rpoB single mutants, as well as stabilization of the expression of rifampin-regulated essential genes and balancing the expression of genes involved in metabolism of sulfur-containing amino acids. Taken together, our data suggest that rpoC mutation may compensate for the fitness defect of rifampicin-resistant M. tuberculosis by altering gene expression in response to rifampin exposure.